Effect of Frying Temperature and Time on the Quality of Small Crispy Meat - Lu ZHANG; Shuangli XIONG; Anlin LI; Dequan XIONG; Dan TANG (Shipin gongye ke-ji, 2024)
The paper investigated the effects of different frying times and temperatures on the quality of small crispy meat. The changes in moisture content, oil content, sensory characteristics, color, thiobarbituric acid value (TBARs value), and pepsin digestibility of small crispy meat were analyzed at 150, 160, 170, 180 and 190 ℃ for 150, 170, 190 and 210 s, respectively. The experimental results showed that with the increase of frying temperature and frying time, the moisture content of small crispy meat significantly decreased (P<0.05), while the oil content significantly increased (P<0.05). The hardness, chewiness, viscosity and elasticity significantly increased (P<0.05), and the value of thiobarbituric acid reactants showed a gradually increasing trend. The digestibility of gastric protease gradually increased with increasing frying time and decreased with increasing frying temperature. The overall moisture content of the small crispy meat for 170 s at 170 ℃ was 44.15%, the moisture content of the meat core was 64.19%, the overall oil content was 50.77%, and the oil content of the meat core was 28.97%. Under this condition, the small crisp meat had moderate hardness, golden color, crisp outside and tender inside, and the best taste.